2018
DOI: 10.2147/prom.s146966
|View full text |Cite
|
Sign up to set email alerts
|

Impact of reslizumab on outcomes of severe asthmatic patients: current perspectives

Abstract: Approximately 5%–10% of asthmatics suffer from severe asthma. New biological treatments represent a great opportunity to reduce asthma burden and to improve asthma patients’ lives. Reslizumab will soon be available in several European countries. This anti-IL-5 IgG4/κ monoclonal antibody, administered intravenously at a dose of 3 mg/kg over 20–50 minutes every 4 weeks, has been shown to be safe and effective in patients with 400 eosinophils/μL or more in their peripheral blood. The clinical effects in reducing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Studies have indicated similar efficacy of this drug in decreasing eosinophil levels in associated asthmatic conditions when administered through intravenous routes, which is also dose-dependent. In both drugs, an increase in serum IL-5 levels following treatment was observed, requiring further study on its long-term efficacy [ 210 , 211 , 212 , 213 ]. In contrast to the aforementioned drugs, benralizumab is an IgG1-type monoclonal antibody against IL-5Rα.…”
Section: Therapeutic Targets For Immunobiologicsmentioning
confidence: 99%
“…Studies have indicated similar efficacy of this drug in decreasing eosinophil levels in associated asthmatic conditions when administered through intravenous routes, which is also dose-dependent. In both drugs, an increase in serum IL-5 levels following treatment was observed, requiring further study on its long-term efficacy [ 210 , 211 , 212 , 213 ]. In contrast to the aforementioned drugs, benralizumab is an IgG1-type monoclonal antibody against IL-5Rα.…”
Section: Therapeutic Targets For Immunobiologicsmentioning
confidence: 99%
“…The standard dose is 100 mg, administered every 4 weeks subcutaneously ( Nucala, 2023 ). Reslizumab (Cinqair ® ) is a recombinant humanized monoclonal antibody (IgG4) that, like mepolizumab, targets IL-5 to prevent its binding with IL-5Rα ( Padilla Galo et al, 2018 ; Cinqair, 2023 ). Reslizumab was approved by the FDA in 2016 as a treatment for patients (≥18 years of age) with severe eosinophilic asthma uncontrolled despite maximum doses of ICS and additional controllers ( Padilla Galo et al, 2018 ; Cinqair, 2023 ).…”
Section: Biological Therapies In Type-2 High Asthmamentioning
confidence: 99%
“…Monoclonal antibodies consist of IgG isotypes: IgG1 (omalizumab, mepolizumab, benralizumab), IgG2, and IgG4 (dupilumab, reslizumab). 16 17 18 19 20 They are characterized by long half-lives and slow clearance, 21 requiring less frequent dosing than is needed for small molecules with shorter half-lives. Pharmacokinetically, monoclonal antibodies show a rapid distribution phase, followed by a slow elimination phase.…”
Section: Pharmacokinetics and Pharmacodynamics Of Monoclonal Antibodiesmentioning
confidence: 99%